Lattice mismatch in Ni3Al-based alloy for efficient oxygen evolution. (20th April 2022) - Li, Shicheng; Liang, Hongyan; Li, Chong; Liu, Yongchang
Highlights: Ni3 Al alloy shows high OER activity and stability. The boosted OER activity was ascribed to the γ/γ' phase lattice mismatch. The increased lattice mismatch facilitated the formation of active β -NiOOH phase. Abstract: The Ni3 Al-based alloy has been considered as a robust catalyst for oxygen evolution reaction (OER) due to its long-term durability and acceptable activity. However, related reports about understanding the catalytic mechanism are rare and desirable. Herein, the effect of γ/γ' phase lattice mismatch on the catalytic performance caused by various cooling rates after solution heat treatment was investigated. With decreasing cooling rate, the morphologies of γ′ precipitates transformed from sphere to cube and the lattice mismatch increased from -0.172% to -0.409%. The increased lattice mismatch facilitated the formation of the active β -NiOOH phase and enhanced the intrinsic catalytic activity, resulting in the optimized OER overpotential of 240 mV at a current density of 10 mA cm −2 with a Tafel slope of 66.1 mV dec −1 and a stability of 200 h in 1 M KOH. This work reveals the lattice mismatch effect on OER and provides a potential candidate for OER.